Effect of different thickeners on quality assurance and consumer preferences in tomato ketchup - SINGH, SUDHIR; SINGH, ASHOK KUMAR; RAI, ASHUTOSH (The Indian Journal of Agricultural Sciences, 2014)
The acceptability of tomato ketchup is dependent on desired mouth feel and acceptable sourness. The acceptable tomato ketchup can be developed with 2.75% corn flour, 7 and 10% of cooked pumpkin and bottle gourd and 0.4% CMC along with 1.5% acidity as acetic acid based on RSM. The vegetable based thickener of bottle gourd and pumpkin in manufacture of tomato ketchup yielded maximum serum separation of 2.2-3.0 ml while negligible serum separation was obtained in tomato ketchup with corn flour and CMC stabilizer. Tomato ketchup with vegetable based thickener of bottle gourd and pumpkin contained maximum (40.17- 57.08 and 41.75-51.79 mg/100g) ascorbic acid, respectively among all the formulations.